2009
DOI: 10.1364/oe.17.005240
|View full text |Cite
|
Sign up to set email alerts
|

Experimental demonstration of distributed feedback semiconductor lasers based on reconstruction-equivalent-chirp technology

Abstract: In this paper we report, to the best of our knowledge, the first experimental realization of distributed feedback (DFB) semiconductor lasers based on reconstruction-equivalent-chirp (REC) technology. Lasers with different lasing wavelengths are achieved simultaneously on one chip, which shows a potential for the REC technology in combination with the photonic integrated circuits (PIC) technology to be a possible method for monolithic integration, in that its fabrication is as powerful as electron beam technolo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
39
0

Year Published

2011
2011
2017
2017

Publication Types

Select...
9

Relationship

4
5

Authors

Journals

citations
Cited by 96 publications
(40 citation statements)
references
References 18 publications
1
39
0
Order By: Relevance
“…The optical spectrum, P-I characteristics and optical field distribution in the cavity of a DFB laser have been previously reported [10], and it has been concluded that DFB lasers based on REC technology have the same optical characteristics as conventional DFB lasers. In 2009, a monolithic 30-wavelength semiconductor laser array was reported based on REC technology [11], and this demonstration further verified the potential applications of REC technology in laser arrays [12].…”
Section: Rec Technologymentioning
confidence: 75%
“…The optical spectrum, P-I characteristics and optical field distribution in the cavity of a DFB laser have been previously reported [10], and it has been concluded that DFB lasers based on REC technology have the same optical characteristics as conventional DFB lasers. In 2009, a monolithic 30-wavelength semiconductor laser array was reported based on REC technology [11], and this demonstration further verified the potential applications of REC technology in laser arrays [12].…”
Section: Rec Technologymentioning
confidence: 75%
“…By tuning injection current of DFB laser diode array, wavelengths of each channel of the array can be tuned [12,13]. Based on reconstruction-equivalent chirp (REC) technology and through employing phase shift, we have realized fourchannel tunable laser array with each laser channel's wavelength can be continuously tuned on a large scale [14,15]. The characteristic of the tunable DFB-LD array used in the experiment is shown in Fig.…”
Section: Resultsmentioning
confidence: 99%
“…Reconstruction equivalent chirp (REC) technique based on sampled grating has been proposed and widely studied to reduce the fabrication cost and improve the laser performances [12][13][14][15][16][17][18][19][20]. As reported in [18], 60-channel DFB laser arrays with high wavelength accuracy and high single-longitudinalmode (SLM) operation was successfully demonstrated.…”
Section: Introductionmentioning
confidence: 99%
“…As reported in [18], 60-channel DFB laser arrays with high wavelength accuracy and high single-longitudinalmode (SLM) operation was successfully demonstrated. In a REC based DFB laser, phase shift or chirp can be equivalently realized by pre-designing sampling pattern and uniform basic (seed) grating [12]. Since the sampled grating with multi-order reflections is used as resonator, the 0th order wavelength must be designed in the non-gain region to ensure the stable SLM operation of 1st or +1st order subgrating.…”
Section: Introductionmentioning
confidence: 99%